Solid‐State Crosslinking of Polysaccharide Electrospun Fibers by Atmospheric Pressure Non‐Equilibrium Plasma: A Novel Straightforward Approach. Issue 11 (8th May 2015) - Liguori, Anna; Paltrinieri, Laura; Stancampiano, Augusto; Gualandi, Chiara; Gherardi, Matteo; Colombo, Vittorio; Focarete, Maria Letizia
Abstract : In this work, the effectiveness of atmospheric pressure non‐equilibrium plasma, generated by a dielectric barrier discharge and operated in air, in successfully crosslinking water soluble pullulan electrospun fibers is demonstrated. After being exposed to plasma, the fibers show a remarkable capability to preserve structural stability and fiber morphology upon water exposure. The gel fraction and the water absorption are quantified to evaluate the crosslinking efficiency of different plasma operating conditions, and ATR‐FTIR characterization provided some insights into plasma‐induced modification of pullulan chemical structure. Abstract : A straightforward crosslinking approach applied to a water soluble polysaccharide directly in the solid state is reported. Atmospheric pressure non‐equilibrium plasma is used for the first time to induce the crosslinking of pullulan electrospun fibers. The proposed approach is highly flexible, cost‐effective and it does not require potentially toxic agents.